Hepatic endothelial notch activation protects against liver metastasis by regulating endothelial-tumor cell adhesion independent of angiocrine signaling - Wohlfeil, Sebastian A.; Schledzewski, Kai; Winkler, Manuel; Zierow, Johanna; Leibing, Thomas; Malek Mohammadi, Mona; Heineke, Jörg; Sticht, Carsten; Olsavszky, Victor; Reiners-Koch, Philipp-Sebastian; Géraud, Cyrill; Goerdt, Sergij (Cancer research, 2019)
The interaction of tumor cells with organ-specific endothelial cells (EC) is an important step during metastatic progression. Notch signaling in organ-specific niches has been implicated in mediating opposing effects on organotropic metastasis to the lungs and the liver, respectively. In this study, we scrutinized the role of endothelial Notch activation during liver metastasis. To target hepatic EC (HEC), a novel EC subtype-specific Cre driver mouse was generated. Clec4g-Cretg/wt mice were crossed to Rosa26N1ICD-IRES-GFP to enhance Notch signaling in HEC (NICDOE-HEC). In NICDOE-HEC mice, hepatic metastasis of malignant melanoma and colorectal carcinoma was significantly reduced. These mice revealed reduced liver growth and impaired metabolic zonation due to suppression of hepatic angiocrine Wnt signaling. Hepatic metastasis, however, was not controlled by angiocrine Wnt signaling, as deficiency of the Wnt cargo receptor Wls in HEC of WlsHEC-KO mice did not affect hepatic metastasis. In contrast, the hepatic microvasculature in NICDOE-HEC mice revealed a special form of sinusoidal capillarization, with effacement of endothelial zonation functionally paralleled by reduced tumor cell adhesion in vivo. Notably, expression of endothelial adhesion molecule ICAM1 by HEC was significantly reduced. Treatment with an anti-ICAM1 antibody significantly inhibited tumor cell adhesion to HEC in wild-type mice confirming that Notch controls hepatic metastasis via modulation of HEC adhesion molecules. As endothelial Notch activation in the lung has been shown to promote lung metastasis, tumor therapy will require approaches that target Notch in an organ-, cell type-, and context-specific manner. Significance: Manipulation of Notch signaling in the endothelium has opposing, organ-specific effects on metastasis to the lung and the liver, demonstrating that this pathway should be targeted in a cell- and context-specific fashion.